Paediatric Gangrenous Caecal Volvulus - Siboe MMW; Omari RO; Lakati KC (The Annals of African Surgery, 2016)
Caecal volvulus though common in adults is rare in children. A 10-year-old boy presented with abdominal pain, distension, vomiting and obstipation of acute onset. An exploratory laparotomy revealed a gangrenous caecal volvulus due to an elongated and mobile right colon. This was treated by a right hemicolectomy and an ileo-transverse anastomosis. He recovered uneventfully. Caecal volvulus should be considered in cases of intestinal obstruction even in the pediatric age group.